Reading Strategies By Indonesian EFL Teachers: A Survey Study - Puji Lestari, Ida (International Research-Based Education Journal, 2023)
This study aims at finding out some reading strategies used by English teachers in Indonesian context during Covid-19 Pandemic and New Normal Era. The participants were 10 English Lecturers majoring English Language and Literature and taking up the lecture of teaching language skills in Cultural Studies Faculty of Universitas Brawijaya Malang. The Metacognitive Awareness of Reading Strategies Inventory (MARSI) was used to collect data about the use of reading strategies while reading academic. The researchers use descriptive qualitative method in collecting the data. The results indicated that participants used each strategy effectively. As the most striking strategy, subjects underlined or circled information in the text to help them remember the information. While both genders preferred to take advantage of similar strategies in common, they mostly preferred to use problem solving strategies compared to other strategies.